A Development of E-Learning System for Standard 1 Malay Subject - See, Tian Zhen; Arbaiy, Nureize (Applied Information Technology And Computer Science, 2022)
The variety of online teaching aids and the lack of comprehensive methods to measure student performance due to limited time in class time cause problems for teachers. As a result, teachers should take the time and effort to tackle these tasks, especially to master these online teaching aids and focus on teaching and assessment. This challenge is the result of no centralized and specialized teaching aids to aid teaching. The content of online teaching aids available today is sometimes not in accordance with the standard syllabus provided by the Ministry of Education and there is no comprehensive evaluation analysis on student performance. Therefore, the effectiveness of the current teaching implementation is limited. Thus, an E-learning system for Malay Subject Year 1 of primary school developed to help diversify learning tools. This project uses the Prototype Model as a methodology and system design based on structured methods. The programming languages used to develop the system are PHP, Javascript, JQuery, and SQL. The system allows students to learn Malay subject through playing quiz, ease the workload of teachers by automatically marking all quiz and provide assessment on the result of all played quiz by students. The system users are student, teacher and administrator. At the end of this project, a fully functional system is expected to help the teaching and evaluation process of student performance.